Virtual geriatric clinics and the COVID-19 catalyst: a rapid review - Murphy, Robert P (Age Ageing, 2020)
BACKGROUND: During the current COVID-19 health crisis virtual geriatric clinics have become increasingly utilised to complete outpatient consultations, although concerns exist about feasibility of such virtual consultations for older people. The aim of this rapid review is to describe the satisfaction, clinic productivity, clinical benefit, and costs associated with the virtual geriatric clinic model of care. METHODS: A rapid review of PubMed, MEDLINE and CINAHL databases was conducted up to April 2020. Two independent reviewers extracted the information. Four subdomains were focused on: satisfaction with the virtual geriatric clinic, clinic productivity, clinical benefit to patients, costs and any challenges associated with the virtual clinic process. RESULTS: Nine studies with 975 patients met our inclusion criteria. All were observational studies. Seven studies reported patients were satisfied with the virtual geriatric clinic model of care. Productivity outcomes included reports of cost-effectiveness, savings on transport, and improved waiting list metrics. Clinical benefits included successful polypharmacy reviews, and reductions in acute hospitalisation rates. Varying challenges were reported for both clinicians and patients in eight of the nine studies. Hearing impairments and difficulty with technology added to anxieties experienced by patients. Physicians missed the added value of a thorough physical examination and had concerns about confidentiality. CONCLUSION: Virtual geriatric clinics demonstrate evidence of productivity, benefit to patients, cost effectiveness and patient satisfaction with the treatment provided. In the current suboptimal pandemic climate, virtual geriatric clinics may allow Geriatricians to continue to provide an outpatient service, despite the encountered inherent challenges.